Assessing Patient Exposure to a Video-Based Intervention in STD Clinic Waiting Rooms: Findings From the Safe in the City Trial. Issue 5 (September 2016) - Besera, Ghenet T.; Cox, Shanna; Malotte, C. Kevin; Rietmeijer, Cornelis A.; Klausner, Jeffrey D.; O'Donnell, Lydia; Margolis, Andrew D.; Warner, Lee
Safe in the City, a video intervention for clinic waiting rooms, was previously shown to reduce sexually transmitted disease (STD) incidence. However, little is known about patients' recall of exposure to the intervention. Using data from a nested study of patients attending clinics during the trial, we assessed whether participants recalled Safe in the City, and, if so, how the intervention affected subsequent attitudes and behaviors. Analyses were restricted to responses to a 3-month follow-up questionnaire among participants who were exposed to the video ( n = 708). Impact was measured as participants' reports of the video's effect on behaviors and attitudes. Associations were evaluated using multivariable logistic regression. Of participants who were exposed, 685 (97%) recalled viewing the video, and 68% recalled all three vignettes. After watching the video, participants felt more positive about condoms (69%) and comfortable acquiring condoms (56%), were reminded of important information about STDs and condoms (90%), and tried to apply what they learned to their lives (59%). Compared with those who recalled viewing one or two vignettes, participants who recalled viewing all three vignettes reported more positive attitudes toward condoms and peer/provider communication. These findings demonstrate that a low-resource video intervention for waiting rooms can provide sufficient exposure to positively influence STD-related attitudes/behaviors.